A STUDY OF REVENUE DIVERSIFICATION FOR ECONOMIC SUSTAINABILITY IN NON PROFIT ORGANISATIONS IN SINGAPORE - Wong, Alan (Global journal of Business and Integral Security, 2023)
This qualitative study revisits the revenue diversification effect on NPOs and their sustainability. It looks into recent developments to focus if there have been new research and considerations explored by Profit organisations, has recent scholars offered new insights into what these success factors are, whether the quality of an NPO is determined by its ability to fundraise or is it a consideration of trans disciplinarian factors. We conducted a desktop survey of Singapore’s NPOs (Focus sector are NPOs for private education and aged care between 2016 to 2020) and applied the research methods and conducted a survey to understand if factors of managerial talent, quality of programs and missional focus supports NPOs who continue to do well. Participants in the surveys will allow us to understand if these traits which appeal to donors and policies to guide subvention from government ensures that resource allocation is done with a set of metrics to ensure better run NPOs continue to do good. Through this research, I am hoping to uncover findings that could point to clearer policy execution and NPO managerial leadership thinking that could guide develop better NPOs in Singapore.